Manufacturing method of manganese sulfate solution

The use of a zeolite with an 8-membered ring structure addresses the challenges of potassium removal from acidic manganese sulfate solutions by enabling efficient and stable selective removal without jarosite formation, thus supporting industrial manganese sulfate production.

JP2025065155AActive Publication Date: 2025-04-17TOSOH CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2025005910
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-12
Filing Date
2025-01-16
Publication Date
2025-04-17
Estimated Expiration
2044-06-10

AI Technical Summary

Technical Problem

Existing methods for removing potassium from acidic manganese sulfate solutions, such as the jarosite method and using manganese dioxide-based adsorbents, face challenges like high iron-based chemical consumption, environmental impact, and instability in acidic environments.

Method used

A method involving the use of a zeolite with a specific structure containing an 8-membered ring, which selectively adsorbs potassium ions from acidic manganese sulfate solutions without forming jarosites, thereby stabilizing the process in acidic environments.

Benefits of technology

This method allows for the efficient and stable selective removal of potassium from manganese sulfate solutions, reducing environmental impact and operational costs, and enabling the production of manganese sulfate solutions suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065155000001
    Figure 2025065155000001
  • Figure 2025065155000002
    Figure 2025065155000002
  • Figure 2025065155000003
    Figure 2025065155000003
Patent Text Reader

Abstract

To provide at least one of an industrially applicable manufacturing method of a manganese sulfate solution, that does not generate jarosite and comprises a step of selectively removing potassium from a sulfuric acid acidic manganese solution; and a manufacturing method of manganese oxide using the manganese sulfate solution.SOLUTION: A manufacturing method of a manganese sulfate solution comprises a step of adsorbing a potassium ion on a zeolite by making a molar ratio of silica to alumina be 6 or more, and bringing the manganese sulfate solution containing the potassium ion into contact with the zeolite containing an oxygen 8-membered ring in a skeletal structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to the selective removal of potassium from acidic manganese sulfate solutions. [Background technology]

[0002] Acid manganese solution is widely used as a raw material for manganese dioxide, etc. Industrially, acid manganese solution is produced by reducing and roasting naturally occurring manganese ore to obtain reduced ore, which is then treated with an acid solution. Since the raw ore contains potassium, it is necessary to remove the potassium in the production of acid manganese solution.

[0003] Manganese sulfate (MnSO4) is an example of a commonly produced acidic manganese solution. In the industrial production of manganese sulfate, a method of removing potassium is widely used in which reduced ore is dissolved in a sulfuric acid solution, an iron-based agent is added to precipitate potassium as jarosite (KFe3(SO4)2(OH)6), and the potassium is removed by solid-liquid separation (hereinafter, also referred to as the "jarosite method") (for example, Patent Documents 1 and 2).

[0004] As a method for removing potassium using an adsorbent, a method has been disclosed in which potassium is removed from a manganese sulfate solution by contacting the solution with a manganese dioxide-based adsorbent (Patent Document 3). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-178749 A [Patent Document 2] JP 2012-219316 A [Patent Document 3] Japanese Patent Application Publication No. 4-31323 [Non-patent literature]

[0006] [Non-Patent Document 1] Chemistry of Materials, 1995, 7, 148-153 Summary of the Invention [Problem to be solved by the invention]

[0007] The jarosite process requires a large amount of iron-based chemicals to produce jarosite, and the facilities and costs involved tend to be large. In addition, jarosite is discharged mixed with slag containing various impurity elements, making it difficult to reuse. Therefore, the slag containing jarosite is disposed of as is in landfills, which places a heavy burden on the environment.

[0008] In contrast, the potassium removal method using a manganese dioxide-based adsorbent disclosed in Patent Document 3 does not involve the formation of jarosite. However, manganese dioxide-based adsorbents are unstable in acidic environments (e.g., Non-Patent Document 1). Therefore, frequent replacement of the adsorbent is required, making it difficult to use the method of Patent Document 3 in industrial production.

[0009] The present disclosure aims to provide at least one of an industrially applicable method for producing a manganese sulfate solution by selectively removing potassium from an acidic manganese sulfate solution without producing jarosite, and a method for producing manganese oxide using the manganese sulfate solution. [Means for solving the problem]

[0010] This disclosure has been carried out to investigate an industrially applicable method for producing a manganese sulfate solution by selectively removing potassium from an acidic manganese sulfate solution. As a result, it has been found that selective removal of potassium from an acidic manganese sulfate solution is possible without the formation of jarosite by applying potassium adsorption using a zeolite with a specific structure. It has also been found that selective removal of potassium from a manganese sulfate solution can be stably performed in an acidic environment.

[0011] That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows. [1] A method for producing a manganese sulfate solution, comprising the steps of contacting a manganese sulfate solution containing potassium ions with a zeolite having a silica to alumina molar ratio of 6 or more and containing an 8-membered oxygen ring in its framework structure, and allowing the potassium ions to be adsorbed onto the zeolite. [2] The method for producing a manganese sulfate solution according to [1] above, wherein the zeolite containing an 8-membered oxygen ring in its skeletal structure is a zeolite having one or more skeletal structures selected from the group consisting of CHA type, FER type, HEU type, MOR type, SZR type, and YFI type. [3] The method for producing a manganese sulfate solution according to [1] or [2] above, wherein the pH of the manganese sulfate solution containing potassium is 6 or less. [4] The method for producing a manganese sulfate solution according to any one of [1] to [3] above, wherein the molar ratio of manganese ions to potassium ions in the potassium-containing manganese sulfate solution is 10 or more and 2,000 or less. [5] A method for producing manganese oxide, using a manganese sulfate solution obtained by the method for producing a manganese sulfate solution according to any one of [1] to [4] above. [6] A method for treating a manganese sulfate solution, comprising a step of contacting a manganese sulfate solution containing potassium ions with a zeolite having a silica to alumina molar ratio of 6 or more and containing an 8-membered oxygen ring in its framework structure, and allowing the potassium ions to be adsorbed onto the zeolite. Effect of the Invention

[0012] The present disclosure can provide at least one of an industrially applicable method for producing a manganese sulfate solution by selectively removing potassium from an acidic manganese sulfate solution without producing jarosite, and a method for producing manganese oxide using the manganese sulfate solution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The method for producing a manganese sulfate solution according to the present disclosure will be described below with reference to an example embodiment. The present disclosure includes any combination of the configurations and parameters disclosed herein, and includes any combination of the upper and lower limits of the values ​​disclosed herein.

[0014] The terms used in this embodiment are as follows.

[0015] An "aluminosilicate" is a composite oxide having a structure consisting of a repeating network of aluminum (Al) and silicon (Si) via oxygen (O). Among aluminosilicates, those that have a crystalline XRD peak in their powder X-ray diffraction (hereinafter also referred to as "XRD") pattern are called "crystalline aluminosilicates", and those that do not have a crystalline XRD peak are called "amorphous aluminosilicates".

[0016] In this embodiment, the XRD pattern can be obtained by XRD measurement under the following conditions.

[0017] Acceleration current / voltage: 40mA / 40kV Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Continuous scan Scan condition: 10° / min Measurement range: 2θ=5° to 40° Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Scattering slit: open Receiving slit: Open Detector: Semiconductor detector (D / teX Ultra2) Filter: Not used The XRD pattern may be measured using a general powder X-ray diffractometer (for example, Ultima IV, manufactured by Rigaku Corporation). The crystalline XRD peak is a peak whose peak top 2θ is identified and detected in the analysis of the XRD pattern using general analysis software, and whose half-width is 2θ=0.10° or less.

[0018] "Zeolite" is a compound in which the skeleton atoms (hereinafter also referred to as "T atoms") have a regular structure with oxygen (O) interposed therebetween, and the T atoms are at least one of metal atoms and metalloid atoms. The metal atoms include at least one selected from the group consisting of aluminum (Al), titanium (Ti), iron (Fe), zinc (Zn), gallium (Ga) and tin (Sn), with aluminum being preferred. The metalloid atoms include at least one selected from the group consisting of boron (B), silicon (Si), germanium (Ge), arsenic (As), antimony (Sb) and tellurium (Te), with silicon being preferred.

[0019] A "zeolite-like substance" is a compound having a regular structure in which T atoms are oxygen-mediated, and the T atoms contain at least an atom other than a metal or a metalloid. Examples of zeolite-like substances include complex phosphorus compounds containing phosphorus (P) as the T atom, such as aluminophosphate (AlPO) and silicoaluminophosphate (SAPO).

[0020] The "skeletal structure" of zeolite or zeolite-like substances (hereinafter also referred to as "zeolite structure") is a skeletal structure specified by the skeletal structure code (hereinafter also referred to simply as "skeleton code") defined by the Structure Commission of the International Zeolite Association. For example, the FER structure is a skeletal structure specified by the structure code "FER". The FER structure can be identified by comparing it with the XRD pattern (hereinafter also referred to as "reference pattern") described in FER of Zeolite Framework Types on the IZA Structure Commission's homepage http: / / www.iza-structure.org / databases / . With respect to the zeolite structure, the skeletal structure, the crystal structure, and the crystal phase are each used synonymously.

[0021] In this embodiment, "-type zeolite" such as "FER type zeolite" means a zeolite having a zeolite structure of the structure code, and particularly means a crystalline aluminosilicate having a zeolite structure of the structure code. In addition, an intergrowth structure of two or more skeletal structures is distinguished from a zeolite consisting of one skeletal structure. For example, a zeolite having an intergrowth structure of CHA type and AEI type (CHA / AEI type) is distinguished from a zeolite having a CHA type skeletal structure and a zeolite having an AEI type skeletal structure, respectively.

[0022] An "8-membered oxygen ring" is a ring structure consisting of eight oxygen atoms and T atoms in between. Hereinafter, it will be expressed as an "n-membered oxygen ring" depending on the number of oxygen atoms, n, that make up the ring.

[0023] "Selectivity" is a ratio defined by the following formula (1), which is the ion exchange rate of a specific ion species (e.g., potassium) relative to the molar amount of ion-exchangeable ions in the zeolite.

[0024] Selectivity [%] = ([M] × n) / [Al] × 100 (1) In equation (1), [M] is the molar concentration [mol / g] of a particular ion species in the zeolite, n is its valence, and [Al] is the molar concentration [mol / g] of aluminum ions in the zeolite.

[0025] [M] and [Al] can be determined by ICP atomic emission spectrometry using a general ICP-AES device (for example, product name: OPTIMA3000DV, manufactured by PERKIN-ELMER).

[0026] The present embodiment will be described below.

[0027] The method for producing a manganese sulfate solution of the present embodiment is a production method (hereinafter also referred to as the "production method of the present embodiment") that includes a step of contacting a manganese sulfate solution containing potassium ions (hereinafter also referred to as the "pre-treatment solution") with a zeolite having a molar ratio of silica to alumina of 6 or more and containing an 8-membered oxygen ring in its framework structure (hereinafter also referred to as the "8-membered ring zeolite"), and adsorbing potassium ions onto the zeolite (hereinafter also referred to as the "potassium removal step"). <8-membered ring zeolite> The zeolite in the manufacturing method of this embodiment is a zeolite containing an 8-membered oxygen ring in the framework structure (hereinafter referred to as "8-membered ring zeolite"). Conventionally, A-type zeolite and X-type zeolite are known as ion exchangers with high heat resistance and high selectivity. However, these zeolites cannot be used as ion exchangers in acidic solutions such as manganese sulfate solutions because their structure collapses in an acidic environment. In contrast, in this embodiment, attention is focused on 8-membered ring zeolites, and an 8-membered ring zeolite having the above-mentioned molar ratio of silica to alumina is used, so that the pre-treatment solution can be treated without structural collapse even in an acidic environment. One of the reasons why 8-membered ring zeolites can be used is that, in addition to the effect of suppressing the release of aluminum ions by the 8-membered oxygen ring, potassium easily enters the pores inside the zeolite of this embodiment, and potassium adsorbed in the zeolite is less likely to be released from the zeolite.

[0028] The eight-membered ring zeolite used in the production method of this embodiment includes zeolites having one or more framework structures selected from the group consisting of AEI type, AFT type, AFX type, CHA type, EAB type, ERI type, ESV type, FER type, GME type, HEU type, KFI type, LEV type, LTA type, LTL type, MAZ type, MEL type, MER type, MFS type, MOR type, MOZ type, MRT type, MWF type, OFF type, PAU type, PTT type, PTY type, PWN type, PWW type, RHO type, RTH type, SFW type, STI type, SZR type, TUN type, UFI type, and YFI type. The eight-membered ring zeolite used in the production method of this embodiment includes zeolites having one or more framework structures selected from the group consisting of AEI type, AFX type, CHA type, EAB type, ERI type, ESV type, FER type, GME type, HEU type, KFI type, LEV type, LTA type, LTL type, MAZ type, MEL type, MER type, MFS type, MOR type, MOZ type, MRT type, MWF type, OFF type, PAU type, PTT type, PTY type, PWN type, PWW type, RHO type, RTH type, SFW type, STI type, SZR type, TUN type, UFI type, and YFI type. Zeolite having one or more skeletal structures selected from the group consisting of CHA type, ERI type, FER type, HEU type, KFI type, LEV type, MEL type, MER type, MFS type, MOR type, MRT type, MWF type, PAU type, PTT type, PTY type, PWN type, RHO type, SFW type, STI type, SZR type, TUN type, UFI type and YFI type, more preferably CHA type, FER type, HEU type, MOR type, SZR type and YFI type, more preferably CHA type and FER type. The 8-membered ring zeolite used in the production method of this embodiment may be an intergrowth structure containing at least one of the above skeletal structures, for example, CHA / AEI type, CHA / AFX type or CHA / GME type.

[0029] In the production method of this embodiment, the 8-membered ring zeolite is preferably at least one of a zeolite containing a 5-membered oxygen ring in addition to an 8-membered oxygen ring in the framework structure, and a zeolite containing an 8-membered oxygen ring as the largest pore, which makes the structure less likely to collapse in an acidic environment.

[0030] Examples of 8-membered ring zeolites containing a 5-membered oxygen ring include zeolites having one or more skeletal structures selected from the group consisting of ESV type, FER type, HEU type, MAZ type, MEL type, MFS type, MOR type, PTY type, PWW type, STI type, SZR type, TUN type, and YFI type, and zeolites having one or more skeletal structures selected from the group consisting of FER type, HEU type, MOR type, SZR type, and YFI type are preferred.

[0031] Examples of 8-membered ring zeolites in which the largest pore contains an 8-membered oxygen ring include zeolites having one or more skeletal structures selected from the group consisting of AEI type, AFT type, AFX type, CHA type, EAB type, ERI type, ESV type, KFI type, LEV type, LTA type, MER type, MRT type, MWF type, PAU type, PTT type, PWN type, RHO type, RTH type, SFW type, and UFI type, and zeolites having a CHA type skeletal structure are preferred.

[0032] In the production method of this embodiment, the 8-membered ring zeolite preferably contains pores with two or more dimensions, which improves the diffusibility of ions and makes them more easily adsorbed.

[0033] Examples of 8-membered ring zeolites containing two-dimensional or higher pores include zeolites having one or more skeletal structures selected from the group consisting of AEI type, AFT type, AFX type, CHA type, EAB type, ERI type, FER type, GME type, HEU type, KFI type, LEV type, LTA type, MAZ type, MEL type, MER type, MFS type, MOZ type, MRT type, MWF type, OFF type, PAU type, PTT type, PTY type, PWN type, PWW type, RHO type, RTH type, SFW type, STI type, SZR type, TUN type, UFI type, and YFI type. Zeolites having one or more skeletal structures selected from the group consisting of CHA type, FER type, HEU type, SZR type, and YFI type are preferred. Zeolites having at least one of the CHA type and FER type skeletal structures are more preferred, and zeolites having a FER type skeletal structure are even more preferred.

[0034] In this embodiment, the molar ratio of silica to alumina in the 8-membered ring zeolite (hereinafter also referred to as "SiO2 / Al2O3 ratio") is 6 or more. When the SiO2 / Al2O3 ratio of the 8-membered ring zeolite is less than 6, the structure is likely to collapse and the 8-membered ring zeolite does not exhibit stable potassium adsorption ability in an acidic environment. For this reason, the SiO2 / Al2O3 ratio of the 8-membered ring zeolite is preferably 6 or more, 8 or more, 10 or more, 13 or more, or 15 or more, and more preferably 100 or less, 80 or less, 50 or less, or 35 or less. Furthermore, in order to achieve the effect of easily increasing the potassium adsorption performance from the pre-treatment solution, the SiO2 / Al2O3 ratio of the 8-membered ring zeolite is preferably 6 or more and 100 or less, 8 or more and 80 or less, or 15 or more and 35 or less.

[0035] In this embodiment, the 8-membered ring zeolite is an aluminosilicate having the above SiO2 / Al2O3 ratio. This makes it possible to expect high durability and potassium adsorption performance in an acidic environment. The 8-membered ring zeolite is preferably a crystalline aluminosilicate.

[0036] In this embodiment, the particle size D50 of the 8-membered ring zeolite is preferably 1 μm or more, 3 μm or more, 5 μm or more, or 7 μm or more, and 20 μm or less, 15 μm or less, or 12 μm or less, in that the potassium ion adsorption performance is likely to be high, and examples of such particle size D50 include 1 μm or more and 20 μm or less, 3 μm or more and 15 μm or more, 5 μm or more and 12 μm or less, or 7 μm or more and 12 μm or less.

[0037] The particle size D50 of 8-membered ring zeolite is the particle size equivalent to the D50 (median size) of the volume particle size distribution obtained by the laser diffraction / scattering method using a general particle size distribution measuring device (for example, the MT-3100II, manufactured by Microtrack Bell). Specific measurement conditions include the following.

[0038] Measurement range: 0.02~2000μm Particle refractive index: 1.66 Particle permeability: permeation Particle shape: non-spherical Solvent refractive index: 1.333 Ultrasonic pretreatment: None In this embodiment, the selectivity of potassium (K) ions of the 8-membered ring zeolite can be 10% or more, 15% or more, or 20% or more. This allows the potassium ions to be adsorbed by efficiently utilizing the ion exchange capacity of the zeolite. It is preferable that the selectivity of potassium ions is high, and examples of the selectivity include 95% or less, 50% or less, or 30% or less, and examples of the selectivity include 10% or more and 95% or less, 15% or more and 50% or less, or 20% or more and 30% or less.

[0039] The selectivity of the potassium ion of the 8-membered ring zeolite can be calculated from the above formula (1) as follows.

[0040] Ion selectivity of potassium ion [%] = ([K] x 1) / [Al] x 100 In this embodiment, the selectivity of manganese (Mn) ions in the 8-membered ring zeolite is preferably 50% or less, 40% or less, or 30% or less. This allows the potassium ions to be adsorbed by efficiently utilizing the ion exchange capacity of the zeolite. The selectivity of manganese ions is preferably low, and is preferably, for example, 0% or more and 50% or less, more than 0% and 50% or less, or further preferably 5% or more and 40% or less.

[0041] The selectivity of manganese ions in 8-membered ring zeolite can be calculated from the above formula (1) as follows.

[0042] Manganese ion selectivity [%] = ([Mn] x 2) / [Al] x 100 (However, all manganese ions adsorbed on the 8-membered ring zeolite are divalent (Mn 2+ ) In this embodiment, the calcium (Ca) ion selectivity of the 8-membered ring zeolite is preferably less than 10%, 7% or less, or 5% or less. This allows the potassium ion to be adsorbed by efficiently utilizing the ion exchange capacity of the zeolite. It is preferable that the calcium ion selectivity is low, for example, 0% or more and less than 10%, more than 0% and less than 10%, or further 1% or more and 5% or less.

[0043] The calcium ion selectivity of the 8-membered ring zeolite can be calculated from the above formula (1) as follows.

[0044] Calcium ion selectivity [%] = ([Ca] x 2) / [Al] x 100 In this embodiment, the selectivity of magnesium (Mg) ions in the 8-membered ring zeolite is preferably less than 10%, 7% or less, or 5% or less. This allows the potassium ions to be adsorbed by efficiently utilizing the ion exchange capacity of the zeolite. The selectivity of magnesium ions is preferably low, and is preferably, for example, 0% or more and less than 10%, more than 0% and less than 10%, or further preferably 1% or more and 5% or less.

[0045] The selectivity of magnesium ions in 8-membered ring zeolite can be calculated from the above formula (1) as follows.

[0046] Ion selectivity of magnesium ion [%]=([Mg]×2) / [Al]×100 In this embodiment, the 8-membered ring zeolite to be subjected to the potassium removal step may be exchanged with any cation, but is preferably exchanged with protons or sodium ions (i.e., the cation type is proton type or sodium type). If potassium ions are partially contained, the ion exchange capacity of the zeolite is substantially reduced, so it is preferable that the potassium ions in the zeolite are as small as possible. The exchange rate of potassium ions relative to the molar amount of ion-exchangeable ions in the 8-membered ring zeolite is preferably 0% or more and 5% or less, more preferably 0% or more and 2% or less.

[0047] The potassium ion exchange rate of the 8-membered ring zeolite can be calculated from the above formula (1) as follows.

[0048] Ion exchange rate of potassium ions [%] = ([K] x 1) / [Al] x 100 The pre-treatment solution used in the manufacturing method of this embodiment is a manganese sulfate solution containing potassium, and in particular, a manganese sulfate solution obtained by dissolving manganese ore with sulfuric acid.

[0049] The pre-treatment solution contains potassium, and the concentration of the potassium ions is, for example, 40 mass ppm or more, 60 mass ppm or more, 80 mass ppm or more, 100 mass ppm or more, or 120 mass ppm or more as the mass ratio of the potassium ions to the pre-treatment solution, and 10000 mass ppm or less, 5000 mass ppm or less, or 1000 mass ppm or less. Specific ranges of the potassium ion concentration of the manganese sulfate solution obtained by dissolving manganese ore in sulfuric acid as the pre-treatment solution include 40 mass ppm or more and 10000 mass ppm or less, 60 mass ppm or more and 5000 mass ppm or less, and further 80 mass ppm or more and 500 mass ppm or less. <Pre-treatment solution> In the pretreatment solution, manganese sulfate was Mn 2+ Ions and SO4 2- Included as ions However, the pre-treatment solution is Mn 2+ The manganese ion may have a different valence from the manganese ion. 3+ Ion, Mn 4+ ions and MnO4 2- The ions may be one or more selected from the group consisting of:

[0050] The manganese ion concentration in the pre-treatment solution may be any concentration that can be used as a raw material for manganese oxide, and may be 1 mass% or more, 2 mass% or more, 3 mass% or more, or 3.5 mass% or more, and 12 mass% or less, 10 mass% or less, or 8 mass% or less, and is preferably 1 mass% or more and 12 mass% or less, 2 mass% or more and 10 mass% or less, or 3 mass% or more and 8 mass% or less.

[0051] "Manganese ion concentration" refers to the concentration of the total amount of manganese ions in a solution. The manganese ion concentration can be determined by ICP atomic emission spectrometry using a general ICP-AES device (for example, product name: OPTIMA3000DV, manufactured by PERKIN-ELMER).

[0052] The molar ratio of manganese ions to potassium ions contained in the pre-treatment solution (hereinafter also referred to as "liquid phase Mn / K molar ratio") may be 10 or more, 50 or more, 100 or more, 150 or more, or 180 or more, and may be 3000 or less, 2500 or less, 1500 or less, 1000 or less, or 800 or less, and the preferred ranges are 10 or more and 3000 or less, 50 or more and 2500 or less, 100 or more and 1500 or less, 150 or more and 1000 or less, and 180 or more and 800 or less. Within these ranges, the potassium concentration of the manganese sulfate solution can be reduced without using excessive zeolite while exhibiting high potassium selectivity.

[0053] The pre-treatment solution may contain ions other than potassium ions and manganese ions. Such ions include at least one of sodium ions, cobalt ions, magnesium ions, and calcium ions, and further at least one of magnesium ions and calcium ions. In order to facilitate selective adsorption of potassium, the selectivity of impurities other than potassium is preferably less than 20%, 10% or less, or 5% or less. The lower the selectivity of impurities other than potassium, the better, but it is preferably 0.1% or more, 0.2% or more, or 0.5% or more. Specific ranges of the selectivity of impurities other than potassium include 0.1% or more and less than 20%, 0.2% or more and 10% or less, or 0.5% or more and 5% or less.

[0054] The manufacturing method of this embodiment may include a step of removing ions other than the potassium ions and manganese ions from the pre-treatment solution (hereinafter, "impurity removing step") prior to the potassium removing step.

[0055] The method for removing ions other than potassium ions and manganese ions from the pre-treatment solution is not particularly limited, and any known method can be used.

[0056] The solvent of the pre-treatment solution may be at least one of water and alcohol, but is preferably water, that is, the pre-treatment solution is an aqueous manganese sulfate solution.

[0057] The pH of the pre-treatment solution is preferably 6 or less. This makes it difficult for manganese oxide to precipitate. In addition, since there is no need to generate jarosite in the method for producing a manganese sulfate solution of this embodiment, there is no need for the pH to be excessively low. Furthermore, in order to make it difficult for dealumination from zeolite to occur, the pH of the pre-treatment solution is preferably 3 to 6, more preferably 4 to 6.

[0058] The pre-treatment solution can be produced by a known method, for example, a method for producing a manganese sulfate solution comprising a step of dissolving naturally occurring manganese ore with sulfuric acid or an aqueous sulfuric acid solution. <Potassium removal process> In the potassium removal step, the method of contacting the 8-membered ring zeolite with the pre-treatment solution includes a method in which the two are uniformly contacted, and examples of the method include a batch method, a continuous method, or a combination of a batch method and a continuous method. An example of a batch method of contacting the zeolite powder with the pre-treatment solution is a method of stirring and mixing the zeolite powder with the pre-treatment solution and performing solid-liquid separation. An example of a continuous method of contacting the zeolite is a method of filling a column or the like with zeolite molded into an arbitrary shape and passing the pre-treatment solution through the column. The continuous method is preferred in terms of high production efficiency of the manganese sulfate solution.

[0059] The contact conditions between the 8-membered ring zeolite and the pre-treatment solution can be set arbitrarily so as to obtain a manganese sulfate solution having an impurity concentration appropriate for the purpose.

[0060] The temperature at which the 8-membered ring zeolite is contacted with the pre-treatment solution is not particularly limited, but examples of the temperature include room temperature (20±10°C), 40°C or higher, 60°C or higher, or 70°C or higher. It is sufficient if the temperature is 100°C or lower, 95°C or lower, or 90°C or lower, and it is preferably 40°C or higher and 100°C or lower, 60°C or higher and 95°C or lower, or 70°C or higher and 90°C or lower.

[0061] The molar ratio of manganese ions to potassium ions contained in the 8-membered ring zeolite after the potassium removal step (hereinafter also referred to as "solid phase Mn / K molar ratio") is preferably lower than the liquid phase Mn / K molar ratio of the pre-treatment solution. This confirms that the 8-membered ring zeolite selectively adsorbs potassium ions from the pre-treatment solution. The value obtained by dividing the liquid phase Mn / K molar ratio of the pre-treatment solution by the solid phase Mn / K molar ratio after contacting the 8-membered ring zeolite with the pre-treatment solution (hereinafter also referred to as "K concentration rate") may be more than 1, and is preferably 20 or more, 50 or more, 100 or more, or 150 or more, and is 1000 or less, 500 or less, or 200 or less, and the range is preferably 20 or more and 1000 or less, 50 or more and 500 or less, or 100 or more and 200 or less. By being in this range, the potassium concentration of the manganese sulfate solution can be reduced with a small amount of zeolite used. By contacting the 8-membered ring zeolite with a sufficient amount of zeolite capable of adsorbing potassium contained in the pre-treatment solution to a target concentration, potassium can be selectively removed from the manganese sulfate acid solution without the formation of jarosite. The ratio of the 8-membered ring zeolite and the pre-treatment solution when contacting them is not particularly limited, but for example, the ratio of the total ion exchange capacity (mol) of the 8-membered ring zeolite used to the potassium ion content of the pre-treatment solution (hereinafter also referred to as "contact ratio") can be set as an index. The contact ratio is preferably 1 or more, 1.5 or more, 2 or more, 3 or more, 4 or more, or 5 or more, and 20 or less, 15 or less, or 10 or less, and the range is preferably 1 or more and 20 or less, 1.5 or more and 15 or less, or 2 or more and 10 or less. By setting it in this range, the 8-membered ring zeolite can be efficiently used to sufficiently adsorb potassium ions.

[0062] The potassium ion concentration in the manganese sulfate solution obtained by the potassium removal step (hereinafter also referred to as the "treated solution") is determined according to the purpose of producing the manganese sulfate solution, and it is sufficient that the potassium ion concentration is lower than that of the pre-treatment solution. The potassium ion concentration of the treated solution is, for example, 80 mass ppm or less, 60 mass ppm or less, 40 mass ppm or less, 20 mass ppm or less, or 10 mass ppm or less, and may also be 0.1 mass ppm or more, 0.3 mass ppm or more, 1 mass ppm or more, 3 mass ppm or more, or 5 mass ppm or more, and the range may be 0.1 mass ppm or more and 80 mass ppm or less, 0.3 mass ppm or more and 60 mass ppm or less, 1 mass ppm or more and 40 mass ppm or less, 3 mass ppm or more and 20 mass ppm or less, or 5 mass ppm or more and 10 mass ppm or less. However, since potassium ions are adsorbed to zeolite, the concentration of the treated solution is inevitably lower than that of the pre-treatment solution.

[0063] The 8-membered ring zeolite subjected to the potassium removal step can be reused by removing the adsorbed potassium ions.

[0064] As a method for removing potassium from the potassium-containing 8-membered ring zeolite after being subjected to the potassium removal step, it is preferable to include a step of contacting the 8-membered ring zeolite subjected to the potassium removal step with a treating agent (hereinafter also referred to as a "regeneration step").

[0065] The treating agent in the regeneration step may be any agent capable of ion-exchanging and removing cations, including potassium, contained in the zeolite, and may be mineral acids, organic acids, metal salts, or ion-exchange resins, preferably mineral acids. As the mineral acid, one or more selected from the group consisting of hydrochloric acid, nitric acid, and sulfuric acid are preferred, and hydrochloric acid is more preferred. EXAMPLES

[0066] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to these examples. <Identification of crystalline phase> An XRD pattern was obtained using a powder X-ray diffractometer (device name: Ultima IV, manufactured by Rigaku Corporation) under the following conditions.

[0067] Acceleration current / voltage: 40mA / 40kV Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Continuous scan Scan condition: 10° / min Measurement range: 2θ=5° to 40° Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Scattering slit: open Receiving slit: Open Detector: Semiconductor detector (D / teX Ultra2) Filter: Not used The crystalline phase of the sample was identified by comparing the obtained XRD pattern with the XRD pattern listed in the Zeolite Framework Types on the IZA Structure Committee homepage http: / / www.iza-structure.org / databases / . <Particle size D50> The particle diameter D50 was determined by measuring the cumulative volume particle size distribution using a laser diffraction / scattering particle size distribution analyzer (device name: Microtrac MT3300EXII, manufactured by Microtrac Bell Co., Ltd.). The measurement conditions are as follows.

[0068] Measurement range: 0.02~2000μm Particle refractive index: 1.66 Particle permeability: permeation Particle shape: non-spherical Solvent refractive index: 1.333 Ultrasonic pretreatment: None The particle diameter D50 [μm] was obtained from the obtained cumulative volume particle size distribution.

[0069] Example 1 FER type zeolite (product name: HSZ (registered trademark)-720KOA: ​​manufactured by Tosoh Corporation, SiO2 / Al2O3 molar ratio: 18.0, cation type: potassium type, K2O content: 5.3 mass%, Na2O content: 1.4 mass%) was subjected to an acid treatment as follows. First, the zeolite was dispersed in 10 times the mass of pure water to obtain a slurry. The obtained slurry was filtered, and 2 mol / L hydrochloric acid (manufactured by Kishida Chemical Co., Ltd.) in an amount of 20 times the mass of the zeolite was poured into the obtained cake. Next, pure water in an amount of 10 times the mass of the zeolite was poured into the cake to wash it. After washing, the cake was dried in the air at 110°C for 15 hours to obtain the zeolite of this example.

[0070] The zeolite in this example was a FER type zeolite (SiO2 / Al2O3 molar ratio: 18.6, cation type: proton type, K2O content: less than 0.1 mass%, Na2O content: less than 0.1 mass%, potassium ion exchange rate: 0%, particle size D50: 10.9 μm).

[0071] Example 2 A cyclohexyldimethylethylammonium (hereinafter also referred to as "CDMEA") hydroxide aqueous solution, a CDMEA bromide aqueous solution, a sodium hydroxide aqueous solution, pure water and amorphous aluminosilicate (SAR: 18.3) were mixed to obtain a raw material composition having the following molar composition.

[0072] SiO2 / Al2O3= 18.3 CDMEA / Si = 0.08 Na / Si = 0.04 K / Si = 0.11 H2O / Si = 15 OH / Si = 0.160 The obtained raw material composition was sealed in a stainless steel autoclave with an internal volume of 80 mL and heated at 150°C for 48 hours while rotating at 55 rpm. The product after heating was separated into solid and liquid, and the obtained solid was washed with 20 times the mass of pure water. The washed solid was dried in the air at 110°C for 20 hours to obtain a crystallized product.

[0073] The obtained crystallized material was calcined in air at 600° C. for 2 hours to obtain a calcined material.

[0074] The acid treatment was carried out in the same manner as in Example 1, except that the fired product was used as the zeolite, to obtain the zeolite of this example.

[0075] The zeolite in this example was a CHA-type zeolite (SiO2 / Al2O3 molar ratio: 19.7, cation type: proton type, potassium ion exchange rate: 0%, Na2O: less than 0.1 mass%, K2O: less than 0.1 mass%).

[0076] Example 3 A sodium hydroxide solution, a potassium hydroxide solution, pure water and amorphous aluminosilicate (SAR: 24.3) were mixed together to obtain a raw material composition having the following molar composition.

[0077] SiO2 / Al2O3= 24.3 Na / Si = 0.13 K / Si = 0.08 H2O / Si = 16 OH / Si = 0.21 The resulting raw material composition was subjected to hydrothermal treatment in the same manner as in Example 2, except that it was heated at 180° C. for 24 hours, to obtain a crystallized product.

[0078] The acid treatment was carried out in the same manner as in Example 1, except that the crystallized product was used, to obtain the zeolite of this example.

[0079] The zeolite in this example was a FER type zeolite (SiO2 / Al2O3 molar ratio: 23.3, cation type: proton type, K2O content: less than 0.1 mass%, Na2O content: less than 0.1 mass%, potassium ion exchange rate: 0%, particle size D50: 9.9 μm).

[0080] Example 4 An aqueous solution of (1-adamantyl)trimethylammonium (hereinafter also referred to as "ATMA") hydroxide, an aqueous solution of sodium hydroxide, pure water and amorphous aluminosilicate (SAR: 25.3) were mixed to obtain a raw material composition having the following molar composition.

[0081] SiO2 / Al2O3= 25.3 ATMA / Si = 0.08 Na / Si = 0.08 K / Si = 0.08 H2O / Si = 18 OH / Si = 0.24 The hydrothermal treatment, calcination treatment and acid treatment were carried out in the same manner as in Example 2, except that the obtained raw material composition was used, to obtain the zeolite of this example.

[0082] The zeolite in this example was a CHA-type zeolite (SiO2 / Al2O3 ratio: 24.7, cation type: proton type, potassium ion exchange rate: 0%, Na2O: less than 0.1 mass%, K2O: less than 0.1 mass%, particle size D50: 5.2 μm).

[0083] Example 5 The zeolite used in this example was MOR type zeolite (product name: HSZ (registered trademark)-640HOA: manufactured by Tosoh Corporation, SiO2 / Al2O3 molar ratio 18.6, cation type: proton type, K2O content: less than 0.1 mass%, Na2O content: less than 0.1 mass%).

[0084] Comparative Example 1 A sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution, pure water and amorphous aluminosilicate (SAR: 12.4) were mixed to obtain a raw material composition having the following molar composition.

[0085] SiO2 / Al2O3= 12.4 Na / Si = 0.14 K / Si = 0.09 H2O / Si = 16 OH / Si = 0.23 The resulting raw material composition was subjected to hydrothermal treatment and acid treatment in the same manner as in Example 3, except that it was heated at 180° C. for 36 hours, to obtain the zeolite of this comparative example.

[0086] The zeolite in this comparative example was a FER type zeolite (SiO2 / Al2O3 molar ratio: 14.1, cation type: proton type, K2O content: 0.3 mass%, Na2O content: less than 0.1 mass%, potassium ion exchange rate: 0%, particle size D50: 53.8 μm).

[0087] Comparative Example 2 FER type zeolite (product name: HSZ (registered trademark)-770HOA: manufactured by Tosoh Corporation, SiO2 / Al2O3 molar ratio: 97.3, cation type: proton type, K2O content: less than 0.1 mass%, Na2O content: less than 0.1 mass%, potassium ion exchange rate: 0%) was used as the zeolite of this comparative example.

[0088] Comparative Example 3 FAU type zeolite (product name: HSZ (registered trademark)-350HUA: manufactured by Tosoh Corporation, SiO2 / Al2O3 molar ratio: 11.1, cation type: proton type, K2O content: less than 0.1 mass%, Na2O content: less than 0.1 mass%, potassium ion exchange rate: 0%) was used as the zeolite of this comparative example.

[0089] Comparative Example 4 FAU type zeolite (product name: HSZ (registered trademark)-373HUA: manufactured by Tosoh Corporation, SiO2 / Al2O3 molar ratio: 30.0, cation type: proton type, K2O content: less than 0.1 mass%, Na2O content: less than 0.1 mass%, potassium ion exchange rate: 0%) was used as the zeolite of this comparative example.

[0090] Comparative Example 5 The zeolite used in this comparative example was an MFI type zeolite (product name: HSZ (registered trademark)-822HOA: manufactured by Tosoh Corporation, SiO2 / Al2O3 molar ratio: 24.0, cation type: proton type, K2O content: less than 0.1 mass%, Na2O content: less than 0.1 mass%, potassium ion exchange rate: 0%).

[0091] Comparative Example 6 Beta zeolite (product name: HSZ (registered trademark)-920NHA: manufactured by Tosoh Corporation, SiO2 / Al2O3 molar ratio: 17.7, cation type: ammonium type, K2O content: less than 0.1 mass%, Na2O content: less than 0.1 mass%) was calcined in air at 600°C for 2 hours to obtain the zeolite of this comparative example.

[0092] The zeolite in this comparative example was beta zeolite (SiO2 / Al2O3 molar ratio: 17.7, cation type: proton type, K2O content: less than 0.1 mass%, Na2O content: less than 0.1 mass%, potassium ion exchange rate: 0%).

[0093] Comparative Example 7 An aqueous solution of ATMA hydroxide, an aqueous solution of sodium hydroxide, pure water and amorphous aluminosilicate (SAR: 13.1) were mixed to obtain a raw material composition having the following molar composition.

[0094] SiO2 / Al2O3= 13.1 ATMA / Si = 0.08 Na / Si = 0.08 K / Si = 0.08 H2O / Si = 18 OH / Si = 0.24 The hydrothermal treatment, calcination treatment and acid treatment were carried out in the same manner as in Example 2, except that the obtained raw material composition was used, to obtain the zeolite of this example.

[0095] The zeolite in this example was a CHA-type zeolite (SiO2 / Al2O3 ratio: 13.6, cation type: proton type, potassium ion exchange rate: 0%, Na2O: less than 0.1 mass%, K2O: less than 0.1 mass%). [Adsorption rating 1] The potassium ion adsorption performance of Examples 1 and 2 was evaluated.

[0096] That is, as a manganese sulfate solution containing potassium, an aqueous solution containing K2SO4, MnSO4, MgSO4, and CaSO4 and having the following composition was prepared and used as pre-treatment solution 1.

[0097] K: 0.0041mol / L (147 mass ppm) Mn: 0.79mol / L (40038 mass ppm) Mg: 0.043mol / L (970 mass ppm) Ca: 0.016mol / L (589 mass ppm) Liquid phase Mn / K molar ratio: 194 pH: 4.5 752 mg of zeolite powder (equivalent to approximately 3 times the contact magnification) was weighed out and added to 100 mL of the pre-treatment solution in a resin container to form a slurry. The slurry was kept at approximately 80°C and shaken at 200 rpm for 20 minutes, after which solid-liquid separation was performed and the filtrate was collected. The solid content was washed by passing 10 times the mass of pure water through the water, and dried in air at 110°C for 4 hours to prepare a measurement sample.

[0098] The concentrations of aluminum, potassium, manganese, magnesium, and calcium in the filtrate and the measurement sample were measured by ICP-AES (product name: OPTIMA3000DV, manufactured by PERKIN-ELMER) and the potassium concentration in the filtrate after the adsorption evaluation (hereinafter also referred to as the "filtrate potassium concentration") and the selectivity of each element were calculated. Furthermore, the solid phase Mn / K molar ratio was calculated from the concentration ratio of manganese and potassium, and the K enrichment rate was calculated.

[0099] The selectivity, solid phase Mn / K molar ratio, K enrichment rate, and filtrate potassium concentration of each measured sample are shown in the table below.

[0100] [Table 1]

[0101] From Table 1, it can be seen that the zeolite of this example can remove potassium from the manganese sulfate solution with a high K concentration rate. In addition, the filtrate potassium concentration was 30 mass ppm in Example 1 and 58 mass ppm in Example 2. From the above results, it can be seen that the manufacturing method of this embodiment can obtain a manganese sulfate solution in which potassium has been selectively removed from the pre-treatment solution. [Durability rating 1] For the measurement sample after the adsorption evaluation 1, a durability evaluation (regeneration step) was carried out by the following method.

[0102] That is, after the adsorption evaluation, a 1N sulfuric acid solution having a mass 100 times that of the measurement sample was passed through the measurement sample at room temperature to remove potassium contained in the measurement sample, and the measurement sample was then washed with water and dried in air at 110°C for 4 hours.

[0103] The composition and XRD pattern of the dried measurement sample were measured in the same manner as above.

[0104] The results of the regeneration process as a durability evaluation are shown in the table below.

[0105] [Table 2]

[0106] It can be seen that the potassium ions adsorbed by the 8-membered ring zeolite of the example are removed by the regeneration process. In addition, the composition of the 8-membered ring zeolite after the regeneration process remains unchanged, and the XRD pattern shows that the initial framework structure is maintained. [Adsorption evaluation 2] The potassium ion adsorption performance of the examples and comparative examples was evaluated.

[0107] That is, as a manganese sulfate solution containing potassium, an aqueous solution containing K2SO4, MnSO4, MgSO4, CaSO4, Na2SO4 and CoSO4 and having the following composition was prepared and used as pre-treatment solution 2.

[0108] K: 0.0053mol / L (209 mass ppm) Mn: 0.664mol / L (33800 mass ppm) Mg: 0.034mol / L (825 mass ppm) Ca: 0.016mol / L (642 mass ppm) Na: 0.038mol / L (897 mass ppm) Co: 0.0004mol / L (24 mass ppm) Liquid phase Mn / K molar ratio: 124 pH: 4.5 1500 mg of the zeolite powder of each of the examples and comparative examples was weighed and added to 45 mL of the pre-treatment solution to prepare a slurry. The slurry was kept at about 80°C and shaken at 500 rpm for 1 hour, after which solid-liquid separation was performed and the filtrate was collected. The solid content was washed by passing 10 times the mass of pure water through the water, and dried in air at 110°C for 4 hours to prepare a measurement sample.

[0109] The concentrations of aluminum, potassium, manganese, magnesium, calcium, sodium and cobalt in the filtrate and the measurement sample were measured by ICP-AES (product name: OPTIMA3000DV, manufactured by PERKIN-ELMER) and the filtrate potassium concentration and the selectivity of each element were calculated. Furthermore, the solid phase Mn / K molar ratio was calculated from the concentration ratio of manganese and potassium, and the K enrichment rate was calculated.

[0110] The selectivity, solid phase Mn / K molar ratio, K enrichment rate, and filtrate potassium concentration of each sample are shown in the table below.

[0111] [Table 3]

[0112] From Table 3, it can be seen that the zeolite of this example can remove potassium from a manganese sulfate solution at a higher K concentration rate than the materials of Comparative Examples 3 to 7, and the filtrate potassium concentration is lower. [Durability rating 2] For the measurement sample after [Adsorption Evaluation 2], durability evaluation 2 (regeneration process) was carried out in the same manner as [Durability Evaluation 1], except that a 2N hydrochloric acid solution having a mass 100 times that of the measurement sample was passed through at room temperature. The results of the regeneration process for durability evaluation 2 are shown in the table below.

[0113] [Table 4]

[0114] From Table 4, it can be seen that the potassium ions adsorbed by the zeolite of this example are removed by the regeneration process. On the other hand, it can be seen that the potassium ions adsorbed by the zeolite of the comparative example are not removed even after the regeneration process, but remain. In addition, the composition of this example after the regeneration process is unchanged, and the XRD pattern shows that the initial framework structure is maintained.

[0115] These results demonstrate that selective removal of potassium from manganese sulfate solution can be stably performed in an acidic environment. [Adsorption evaluation after regeneration treatment] The evaluation was carried out in the same manner as in [Adsorption evaluation 2], except that 1000 mg of the zeolite powder of the examples and comparative examples obtained in [Durability evaluation 2] was weighed out and added to 30 mL of the pre-treatment solution to form a slurry.

[0116] The selectivity, solid phase Mn / K molar ratio, K enrichment rate, and filtrate potassium concentration of each sample are shown in the table below.

[0117] [Table 5]

[0118] From Table 5, it was found that the zeolites of the examples were able to selectively remove potassium ions repeatedly even after the adsorbed potassium ions had been removed by a regeneration step.

[0119] From these results, the production method of the present embodiment was a method for producing a manganese sulfate solution that can selectively remove potassium ions from the manganese sulfate solution in an acidic environment, and thus was capable of suppressing the generation of jarosite. In addition, since potassium ions can be repeatedly removed by subjecting the 8-membered ring zeolite to a regeneration step, the method was an industrially applicable method for producing a manganese sulfate solution that does not require frequent replacement. [Industrial Applicability]

[0120] The method for producing a manganese sulfate solution according to the present disclosure can be usefully used in applications in which a manganese sulfate solution is produced by selectively removing potassium from an acidic manganese sulfate solution using an industrially applicable adsorbent without the formation of jarosite.

[0121] In addition, the manganese sulfate solution obtained by this production method can be used as a raw material for manganese oxide.

Claims

1. A potassium-adsorbing zeolite having a molar ratio of silica to alumina of 15 or more and 80 or less and containing an 8-membered oxygen ring in its framework structure, which adsorbs potassium ions from an acidic manganese sulfate solution containing potassium ions.

2. 2. The potassium-adsorbing zeolite according to claim 1, which has one or more framework structures selected from the group consisting of CHA type, FER type, HEU type, MOR type, SZR type and YFI type.

3. 3. The potassium-adsorbing zeolite according to claim 1 or 2, having a particle diameter D50 of 1 μm or more and 20 μm or less.

4. 3. The potassium-adsorbing zeolite according to claim 1, which has a selectivity for potassium (K) ions of 10% or more and 95% or less.

5. 3. The potassium-adsorbing zeolite according to claim 1, wherein the selectivity for manganese (Mn) ions is 0% or more and 50% or less.

6. 3. The potassium-adsorbing zeolite according to claim 1, wherein the potassium ion exchange rate is from 0% to 5%.

Citation Information

Patent Citations

  • Preparation method of high-purity manganese sulfate solution

    CN102502854A

  • Medical adsorbent

    JP1979060285A

  • Inorganic ion exchanger, its production and metallic ion removing method

    JP1998015401A

  • Xenon adsorbent

    JP2019077603A

  • YFI type zeolite, method for producing the same, hydrocarbon adsorbent, and hydrocarbon adsorption method

    JP2022185584A